Service Innovation and Licensing Service Quality as Determinants of Business Operator Satisfaction - Ernita; Rosidi; Umi Muawanah (Al-Qalam Institue, 2026)
This study examines the influence of service innovation and licensing service quality on business operator satisfaction at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Probolinggo Regency. The research employs a quantitative approach with a sample of 95 business operators who received licensing services. Data were collected through Google Forms questionnaires and analyzed using multiple linear regression with SPSS 25. The findings reveal that licensing service innovation does not significantly affect business operator satisfaction, while licensing service quality—comprising tangibles, reliability, responsiveness, assurance, and empathy—has a positive and significant impact on satisfaction. When examined simultaneously, both service innovation and service quality significantly influence business operator satisfaction. This study confirms that improving public service quality, particularly in aspects of reliability, responsiveness, assurance, empathy, and tangible evidence, is the primary factor in creating satisfaction among business operators in Probolinggo Regency.